Community-based resource management in an upland and a coastal community in Bacungan, Puerto Princesa - Roa, Shellemai A.; Capinig, Erwin R.; Yap, Jeneferlyn; Buncag, Mark Joseph J.; Caabay, Jessa Marie S.; Baabo, Russel Jones T.; Bero, Roy O.; Villagracia, Ritchelle N.; Docto, Sheryl G.; Valencia, Dexter G. (2015)
Community-based resource management is on of the strategies employed by the Philippine government as it devolves its powers to communities under the Local Government Code of 1991. Decentralization ensures equity and accessibility to natural resources. In an attempt to assess the gains of decentralization, the researchers examined two community-based resource management programs in Barangay Bacungan, Puerto Princesa City. The study area consisted of a coastal and an upland community, namely Sitio Candis III and Sitio San Carlos, respectively. The team inquired about the issues experienced in these communities concerning resource management, and the programs and strategies implemented to address the identified issues and the effectiveness of the approach to the stakeholders involved. Common issues identified in both communities are uncontrolled timber cutting and lack of livelihood opportunities. Operation Bantay Gubat, the establishment of cooperatives and formulation of community-based management plans were the observed strategies and programs imposed in both communities. Participation by the community was highly effective and relevant to needs of the community as reflected in the results of the interview.
Keywords: Community based resource management; Resource management